O uso do transmídia storytelling para auxiliar crianças a mudar o hábito de chupar o dedo - Barranco, Tatiana Gonçalves (Universidade do Vale do Rio dos Sinos, 2017)
This research aims to comprehend how the creative economy, through the Transmedia Storytelling, can help children from three years old on to change the thumb-sucking habit. Therefore, primarily, a theoretical basis on the given topics is performed. The referred subjects are creative economy, Transmedia Storytelling and the social-interactionist development that states knowledge and learning are built on exchanges that are established between the individual and the environment, which can be stimulated. In order to elucidate these links, as specific objectives, this paper pursues to comprehend the application of Transmedia Storytelling in the creative economy; understanding how the Transmedia Storytelling can help children overcome the habit of thumb-sucking; and it proposes a creative economy final product, resulting from Transmedia Storytelling, to support children from three years old on to change the habit of sucking their thumbs. In order to enable a relevant product, the study performed a qualitative research, with an exploitative approach, from in depth interviews, by a sample of the target public for instance educators, psychologists, phonoaudiologists and parents. As a result, it suggests, as major media, the development of a book which tells a story for a child, who has the thumb-sucking habit and orchestrates parents and professionals in the changing process of this habit; and as secondary media, the development of a non-digital game.
Keywords: Economia criativa; Transmídia storytelling; Desenvolvimento Infantil; Interações; Creative economy; Transmedia storytelling; Child development; Interactions